Violence in primary care: Prevalence and follow-up of victims - Favrat Bernard (BMC Family Practice, 2006)
Abstract Background Primary care physicians underestimate the prevalence of domestic violence and community violence. Victims are therefore at risk of further episodes of violence, with psychological and physical consequences. We used an interview to assess the prevalence of domestic and community violence among Swiss natives and foreigners. In a follow-up study, we evaluated the consequences of the interview for the positive patients. Methods We evaluated the prevalence of violence by use of a questionnaire in an interview, in an academic general internal medicine clinic in Switzerland. In a follow-up, we evaluated the consequences of the interview for positive patients. The participants were 38 residents and 446 consecutive patients. Questionnaires were presented in the principal language spoken by our patients. They addressed sociodemographics, present and past violence, the security or lack of security felt by victims of violence, and the patients' own violence. Between 3 and 6 months after the first interview, we did a follow-up of all patients who had reported domestic violence in the last year. Results Of the 366 patients included in the study, 36 (9.8%) reported being victims of physical violence during the last year (physicians identified only 4 patients out of the 36), and 34/366 (9.3%) reported being victims of psychological violence. Domestic violence was responsible for 67.3% of the cases, and community violence for 21.8%. In 10.9% of the cases, both forms of violence were found. Of 29 patients who reported being victims of domestic violence, 22 were found in the follow-up. The frequency of violence had diminished (4/22) or the violence had ceased (17/22). Conclusion The prevalence of violence is high; domestic violence is more frequent than community violence. There was no statistically significant difference between the Swiss and foreign patients' responses related to the rates of violence. Patients in a currently violent relationship stated that participating in the study helped them and that the violence decreased or ceased a few months later.